2023
DOI: 10.1111/tpj.16317
|View full text |Cite
|
Sign up to set email alerts
|

Targeted mutagenesis of the vacuolar H+ translocating pyrophosphatase gene reduces grain chalkiness in rice

Peter James Icalia Gann,
Dominic Dharwadker,
Sajedeh Rezaei Cherati
et al.

Abstract: SUMMARYGrain chalkiness is a major concern in rice production because it impacts milling yield and cooking quality, eventually reducing market value of the rice. A gene encoding vacuolar H+ translocating pyrophosphatase (V‐PPase) is a major quantitative trait locus in indica rice, controlling grain chalkiness. Higher transcriptional activity of this gene is associated with increased chalk content. However, whether the suppression of V‐PPase could reduce chalkiness is not clear. Furthermore, natural variation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 80 publications
1
6
0
1
Order By: Relevance
“…The resulting mutants showed 5 to 12-fold suppression of VPP5 in the caryopses, a relatively higher level of PPi, and enhanced expression of PPi-dependent enzyme genes, Fructose-6P 1phosphotransferase PPi (PFP), Pyruvate, orthophosphate dikinase (PPDK), and UGPase, indicating the effect of VPP5 on metabolic processes in the developing grains. Accordingly, vpp5 lines contained higher starch content and lower chalk in the mature grains, and most importantly, resisted chalk formation under high nighttime temperatures, a major inducer of grain chalkiness in rice (Gann et al, 2023). This study also found post-germinative growth defect in the vpp5 lines that was rescued by sucrose in the media.…”
Section: Introductionsupporting
confidence: 58%
See 4 more Smart Citations
“…The resulting mutants showed 5 to 12-fold suppression of VPP5 in the caryopses, a relatively higher level of PPi, and enhanced expression of PPi-dependent enzyme genes, Fructose-6P 1phosphotransferase PPi (PFP), Pyruvate, orthophosphate dikinase (PPDK), and UGPase, indicating the effect of VPP5 on metabolic processes in the developing grains. Accordingly, vpp5 lines contained higher starch content and lower chalk in the mature grains, and most importantly, resisted chalk formation under high nighttime temperatures, a major inducer of grain chalkiness in rice (Gann et al, 2023). This study also found post-germinative growth defect in the vpp5 lines that was rescued by sucrose in the media.…”
Section: Introductionsupporting
confidence: 58%
“…Rice vpp5 mutants show downregulation of vacuolar H + translocating pyrophosphatase (V-PPase) gene in the developing caryopses, which correlates with the accumulation of PPi and an altered rate of starch metabolism during grain lling. These mutants showed a relatively slower post-germinative growth, which could be rescued by the exogenous supply of sucrose (Gann et al, 2023). By regulating cellular pH and PPi concentration, V-PPases regulate metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations